Efficacy of golimumab in treating uveitis in patients with ankylosing spondylitis - T. V. Dubinina; Sh. F. Erdes (Современная ревматология)
The paper presents the results of recent studies of the efficacy of golimumab (GLM) in the treatment of uveitis in patients with ankylosing spondylitis (AS). The data obtained in these studies suggest that GLM is highly effective in relieving and preventing uveitis attacks. However, all the given studies have a number of disadvantages; primarily they have included a limited number of patients. Further prospective randomized clinical trials with large sample sizes are required to evaluate the efficacy and safety of GLM for the treatment of uveitis in patients with spondyloarthritis.